1, 3-Dibromo-5, 5-dimethylhydantoin (DBH) mediated one-pot syntheses of α-bromo/amino ketones from alkenes in water. Issue 48 (18th November 2016) - Xu, Senhan; Wu, Ping; Zhang, Wei
Abstract : 1, 3-Dibromo-5, 5-dimethylhydantoin (DBH) served as a dual-role reagent in one reaction, providing a direct and environmentally benign access toward α-bromo/amino ketones in water. Abstract : α-Bromo ketones are versatile intermediates of high practical utility. Traditional approaches to these compounds are restricted to a relatively hazardous/complex reagent combination, a long reaction time, the use of non-environmentally friendly solvents, or a limited substrate scope. Herein, we describe the development of a new methodology for the preparation of α-bromo ketones from alkenes using 1, 3-dibromo-5, 5-dimethylhydantoin (DBH) as a bromine source and an oxidant simultaneously. This easy to carry out two-step one-pot protocol proceeds in water and provides high yield of a great variety of α-bromo ketones. Addition of an amine to the intermediate α-bromo ketone further enables the preparation of α-amino ketones in a one-pot sequence.